Pengaruh Kepemilikan Aset Investasi, Pengetahuan Bisnis Online, Literasi Keuangan dan Ekspetasi Pendapatan Terhadap Minat Bisnis Online Era Pandemi COVID-19 - Fatimah Pohan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Individual economic development is very easy and affordable by what each individual has and the environment also helps someone in the success of each individual, especially after the presence of the internet provides many benefits and opportunities for society to achieve goals on a large scale, the internet is also help make it easier for the community to deal with the problem of the economic crisis due to the conditions of the Covid-19 pandemic era which made many people have to accept jobs because of the difficulty of the community in being able to carry out activities together and closely because the epidemic is contagious so that people must be able to adjust to open opportunities to be able survive and revive the economy during the Covid-19 pandemic era, one of which is by opening up their own business opportunities using the internet which is commonly known as buying and selling online, but many people are not biased. how many factors, in this study will look at the influence of asset ownership, business knowledge, financial literacy and income expectations that will be achieved if you do business online in the era of the Covid-19 pandemic.